Peran Relawan Pajak untuk Negeri (Renjani) Ditinjau Melalui Komunikasi Strategis dan Divusi Inovasi - Yeni Nuraeni; Beny Susanti; Feni Andriani; Dewi Putrie Lestari; Nola Marina (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to determine the role of Tax Volunteers for the Country in the implementation of the Renjani program reviewed through Strategic Communication and diffusion of innovation. Used Qualitative methodology with a constructivist paradigm. The results of the study indicate that the role of Tax Volunteers for the Country (Renjani) is something valuable for individuals who care about national development through tax contributions.  Members will be part of community involvement efforts through various activities, such as assistance in reporting Annual Tax Returns, tax public relations activities, and other related activities. Reviewed through Strategic Communication, it can be clearly seen through the elements of Purposeful Communication, Audience-centered, Message Consistency, Organizational Alignment, and Long-term Orientation. Reviewed through  diffusion of innovation, it can be seen through the elements of Innovation, Communication channels, and Social systems.